Aesthetics and Politics: The Afterlives of Oscar Wilde’s The Soul of Man Under Socialism (1891) - Xavier GIUDICELLI (E-REA)
Oscar Wilde is regarded as the emblematic figure of Aestheticism and Art for Art’s sake and thus of the autonomisation of the arts in late nineteenth-century Britain. That is why The Soul of Man under Socialism, his most overtly political essay, published in The Fornightly Review in February 1891, has often baffled critics and elicited contradictory responses. This article shows how The Soul of Man under Socialism articulates politics and aesthetics and it looks into its afterlives, in particular its publishing history in Europe in the twentieth and twenty-first centuries as well as some of the readings and reinterpretations it has prompted in the academic field, more specifically the political uses of this essay in the context of British queer theory. The aim of the article is to highlight the way Wilde’s essay reflects and problematizes the uneasy negotiation between words and action, aesthetics and politics, art and commitment and raises questions that are still relevant today.